Female infants are more susceptible to the effects of maternal antenatal depression; findings from the Pelotas (Brazil) Birth Cohort Study - Netsi, Elena (J Affect Disord, 2020)
BACKGROUND: We utilised data from the 2015 Pelotas Birth Cohort, a large prospective cohort in southern Brazil, to examine the association of moderate and severe antenatal depression with child birth outcomes and explore interactions with sociodemographic characteristics. METHODS: Data was available for n = 3046 participants and their infants. We measured antenatal depression using the Edinburgh Postnatal Depression Scale (EPDS, ≥13 for moderate and ≥17 for severe depression). Outcome measures included gestational age, birth weight, length and head circumference, using the Intergrowth-21st standards. We controlled for known confounders including obstetric risk. RESULTS: We did not find differences in childbirth outcomes by maternal depression status for participants with at least moderate depression, although there was an increased risk for female offspring to be small for gestational age (SGA, OR 2.33[1.37,3.97]). For severe depression (EPDS≥17) we found an increased risk for lower APGAR scores (OR 1.63[1.02,2.60]) and being SGA (OR 1.77[1.06,2.97], with an increased risk for female offspring in particular to be in lower weight centiles (−10.71 [−16.83,−4.60]), to be SGA (OR 3.74[1.89, 7.44]) and in the lower 10th centile for length (OR 2.19[1.25,3.84]). LIMITATIONS: include the use of a maternal report questionnaire to ascertain depressive symptoms. CONCLUSIONS: In this recent large longitudinal cohort in Brazil we did not find independent effects of depression on adverse birth outcomes or interactions with sociodemographic characteristics. We found an increased risk of being SGA for female offspring of women with moderate and severe depression, in line with other research suggesting females may be more susceptible to antenatal disturbances. FUNDING: This work was supported by the Wellcome Trust, United Kingdom (095582), the Brazilian National Research Council (CNPq) and the Coordination for the Improvement of Higher Education Personnel (CAPES). EN was supported by the UK Economic and Social Research Council GCRF Postdoctoral Fellowship (ES/P009794/1).